One Step up the Ladder of Prebiotic Complexity: Formation of Nonrandom Linear Polypeptides from Binary Systems of Amino Acids on Silica. Issue 5 (20th December 2018) - Sakhno, Yuriy; Battistella, Alice; Mezzetti, Alberto; Jaber, Maguy; Georgelin, Thomas; Michot, Laurent; Lambert, Jean‐François
Abstract: Evidence for the formation of linear oligopeptides with nonrandom sequences from mixtures of amino acids coadsorbed on silica and submitted to a simple thermal activation is presented. The amino acid couples (glutamic acid+leucine) and (aspartic acid+valine) were deposited on a fumed silica and submitted to a single heating step at moderate temperature. The evolution of the systems was characterized by X‐ray diffraction, infrared spectroscopy, thermosgravimetric analysis, HPLC, and electrospray ionization mass spectrometry (ESI‐MS). Evidence for the formation of amide bonds was found in all systems studied. While the products of single amino acids activation on silica could be considered as evolutionary dead ends, (glutamic acid+leucine) and, at to some extent, (aspartic acid+valine) gave rise to the high yield formation of linear peptides up to the hexamers. Oligopeptides of such length have not been observed before in surface polymerization scenarios (unless the amino acids had been deposited by chemical vapor deposition, which is not realistic in a prebiotic environment). Furthermore, not all possible amino acid sequences were present in the activation products, which is indicative of polymerization selectivity. These results are promising for origins of life studies because they suggest the emergence of nonrandom biopolymers in a simple prebiotic scenario. Abstract : An issue of some complexity : The activation of single amino acids on mineral surfaces causes polymerization of peptides, but is often limited to disappointingly simple molecules (see figure). Two special systems consisting in couples of amino acids on silica (Glu+Leu and Asp+Val) were observed to give long linear peptides (up to hexamers), with indications of sequence selectivity, raising the interest in such systems for origins of life studies.